2022
DOI: 10.7554/elife.65310
|View full text |Cite
|
Sign up to set email alerts
|

Identification of autosomal cis expression quantitative trait methylation (cis eQTMs) in children’s blood

Abstract: Background:The identification of expression quantitative trait methylation (eQTMs), defined as associations between DNA methylation levels and gene expression, might help the biological interpretation of epigenome-wide association studies (EWAS). We aimed to identify autosomal cis eQTMs in children’s blood, using data from 832 children of the Human Early Life Exposome (HELIX) project.Methods:Blood DNA methylation and gene expression were measured with the Illumina 450K and the Affymetrix HTA v2 arrays, respect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 64 publications
4
19
0
Order By: Relevance
“…Stratifying DNAm sites with respect to their location on the assessed transcript, we found that DNAm sites situated in the first exon and nearby the TSS were enriched for negative effects ( P = 2.7e-3, 1.2e-5 and 3.8e-4 for 1st exon, TSS ± 1500 bp and TSS ± 200 bp, respectively), whereas those in the gene body were enriched for positive ones ( P = 2.2e-10; Supplementary Table 3) . These observations are in line with previous studies that only showed a slight trend for negative methylation-gene expression correlations 36 39 . We further tested whether the MR DNAm-to-transcript causal effects correlated with reported methylation-transcript correlations 37 and found a strong agreement ( ρ = 0.39, P = 2.6e-18, 471 DNAm-transcript pairs).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Stratifying DNAm sites with respect to their location on the assessed transcript, we found that DNAm sites situated in the first exon and nearby the TSS were enriched for negative effects ( P = 2.7e-3, 1.2e-5 and 3.8e-4 for 1st exon, TSS ± 1500 bp and TSS ± 200 bp, respectively), whereas those in the gene body were enriched for positive ones ( P = 2.2e-10; Supplementary Table 3) . These observations are in line with previous studies that only showed a slight trend for negative methylation-gene expression correlations 36 39 . We further tested whether the MR DNAm-to-transcript causal effects correlated with reported methylation-transcript correlations 37 and found a strong agreement ( ρ = 0.39, P = 2.6e-18, 471 DNAm-transcript pairs).…”
Section: Resultssupporting
confidence: 93%
“…Interestingly, MPs were higher when DNAm was downregulating rather than upregulating transcripts. Previous genome-wide methylation and gene expression association studies reported high fractions of positive correlations (30–41%) 36 , 37 , 39 and further investigations indicated that our estimated methylation-to-transcript causal effects agree strongly with the respective correlations reported by Grundberg et al ( P =2.6e-18). While poorly understood 38 , several mechanisms have been proposed to explain the phenomenon of DNAm induced transcription: preferential binding of some transcription factors to methylated DNA 53 , 54 , prevention of repressor binding indirectly leading to increased expression through looping DNA 24 , 55 , or DNAm in the gene body promoting elongation efficiency and preventing spurious initiation of transcription 56 .…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This CpG is located in a promoter, and is 987 bp downstream of gene CCDC115 (Coiled-Coil Domain Containing 115) and 4791 bp upstream of gene IMP4 (IMP U3 Small Nucleolar Ribonucleoprotein 4) (Figure s4). In blood, the methylation level of this CpG was positively associated with the mRNA expression of IMP4 (PeQTM=9.7*10 -7 ), as reported by a recent eQTM (expression quantitative trait methylation) study (60). In brain, the methylation levels of cg01331772 and the mRNA expression of IMP4 were genetically positively correlated in our OMIC-based SMR analysis (BetaSMR=0.35, PSMR_adjusted=8.4x10 -4 , PHEIDI_unadjusted=0.1).…”
Section: An Aging-associated Atypical Poe Co-methylation Network (Mod...supporting
confidence: 85%
“…First, we paired each transcript cluster (TC) to all CpGs closer than 500 kb from its transcription start site (TSS), and then, for each CpG-TC pair we fitted a linear regression model between gene expression and methylation levels adjusted for age, sex and cohort. More details on the analyses and the multiple-testing correction can be found in Supplementary Information and elsewhere 114 .…”
Section: Expression Quantitative Trait Methylation (Eqtms) and Mirna ...mentioning
confidence: 99%